Biostimulant and substrates on litchi tree propagation by air layering - Souza, Jackson Mirellys Azevêdo [UNESP] (2016)
The production of quality seedlings is important for the crop cycle and the main propagation type is by the air layering technique, which can be enhanced by using different substrates and plant growth regulators. Therefore, the objective of this study was to evaluate the use of a biostimulant and substrate types in the propagation of litchi tree by air layering. The experiment was installed in a commercial area in the city of Mogi Mirim, SP, Brazil and conducted in a randomized block design with a 5×2 factorial with four replications. The treatments consisted of five Stimulate® biostimulant concentrations (0, 3, 6, 9, and 12 ml L-1) and two substrate types (Plantmax® and earthworm humus). After 120 days, the root length (cm), number of roots, calloused and rooted layers percentage (%), root fresh and dry mass (g) and root volume (cm3) were evaluated. Based on the results, it was found that the concentrations of 6.1 and 6.9 ml L-1 promoted greater success in litchi tree propagation and that the layers can be produced on both evaluated substrates.